Reactivity of aragonite with dicalcium phosphate facilitates removal of dental calculus - Amir Elhadad (18192829) (2025)
Dental calculus, a main contributor of periodontal diseases, is mostly composed of inorganic calcium phosphate species such as dicalcium phosphate, whitlockite, octa calcium phosphate, and hydroxyapatite. Under physiological pH 7.4, dicalcium phosphates can gradually interact with calcium carbonate to form hydroxyapatite. Therefore, we hypothesized that aragonite (Arg) could react with dental calculus, facilitating its removal. To assess the reactivity of Arg with dental calculus, we examined the changes in surface morphology, composition, and topography of Arg and dental calculus upon exposure to each other in an aqueous environment. The impact of Arg on the removal of dental calculus was assessed by brushing polished sections of dental calculus, enamel, and dentin with slurries of Arg and measuring the depth of abrasion using a stylus profilometer. Our results demonstrate that Arg can react with dental calculus in aqueous environment. This reaction increases calculus surface roughness which in turn facilitate dental calculus removal by brushing. Aragonite could be a promising abrasive for toothpaste design for management of dental calculus. Other Information Published in: Journal of Materials Science: Materials in Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10856-025-06867-6